Picture postcards sent from Japan by Austro-Hungarian navy members - Shigemori Bučar, Chikako (Array, 2019)
Many of the old Japanese postcards archived in Slovenia today date from the period between the 1890s and 1920s when Austro-Hungarian Navy members were active and travelled to Japan as a part of their duties. Collectors and users of these postcards were of Slovenian origin. Their postcards were identified in the National and University Library in Ljubljana and in the Maritime Museum “Sergej Mašera” Piran. A postcard in private possession has also been added to the list. The format regulation of postcard printing changed in Japan in 1907 and this is confirmed using the postcards identified in Slovenia. The main motifs of the pictures were of scenery, portraits and individual objects. Among them, the category of scenery is dominated by ports, such as Yokohama, Kobe and Nagasaki, which are later overtaken as they become tourist destinations. The most characteristic postcards from this period around the turn of the century fall under the category of portrait: clothing and hairdos, customs and professions were all the focus of attention. These photos were made in photo studios with the aim of introducing Japan and its culture to Western visitors. As for the category of individual objects, picture postcards of Russian and Japanese warships attract our eyes.